Assessement of locally available sports bras based on needs of selected Filipina sports bra users - Guilas, Paola Bianca Y.
In order to design and manufacture effective products, in this case, sports bras, it is necessary to do a market analysis of consumer needs and wants (Bowles, Steele, & Munro, 2012). The general objective of the study was to assess locally available sports bras in relation to addressing the needs of selected Filipina sports bra users. Specifically, the study aimed to determine the needs of selected Filipina sports bra users based on their identified motivations, preferences, and satisfaction on locally available sports bras, describe locally available sports bra products, and identify areas of improvement for locally available sports bras. The study made use of the descriptive method of research and gathered both qualitative and quantitative data. Data was obtained through focus group discussions (FGD) and an online survey. Using non-probability sampling, respondents totalled to 316, 12 for the FGD and 304 from the online survey. Comfort and support emerged as the top two motivations for wearing sports bra. Most of the locally available sports bras surveyed generally cater to the preferences of the selected Filipina sports bra consumers with the exception of specific underband and strap measurements. Among the categories for preferences, comfort ranked first followed by fit, support, affordability, aesthetic, and lastly, washability. In terms of satisfaction, majority of the respondents are generally satisfied with the products available in the market. However, majority of those from the large cup class were dissatisfied due to complications on sizing and fit. Majority of the respondents also believe that locally available sports bras could still be improved in terms of more designs or styles, sizing, and affordability. It is recommended to conduct a study which focuses on specific aspects such as the sports bra needs of petite or plus size women. More extensive studies on which type of sports bra provides better support and comparisons of local and international sports bras could also be done to further increase knowledge on sports bras in the future.